Metaphors in the reporting of lottery winners in Malaysian news articles / Mohammad Huzaifa Siddiqui - Mohammad Huzaifa, Siddiqui (2019)
The Malaysian news media seems to play an important role in highlighting the winners of lotteries, and it is observed that metaphors are commonly deployed in telling the narrative of these winners. In this research, these metaphors are investigated in order to examine how they create an imaginary reality such as lottery winning is an easy task. The news articles from the four most distributed Malaysian English newspapers have been curated. The analytical framework is carried out using Charteris-Black’s (2004) three stages of Critical Metaphor Analysis approach: identification, interpretation, and explanation. The study shows that, despite the low odds of winning the lottery in Malaysia and its likely negative outcomes, lottery gaming is portrayed as a game, a sport, or a pleasant journey which results in the participant becoming a millionaire or a billionaire. It is also argued in this research that these messages can be harmful. Such use of metaphoric domains gives birth to fantasies of winning and they tap into irrational behavior of desires. It is hoped the analysis of metaphors will facilitate critical awareness amongst news readers.